Sonoelastography in the diagnosis of thyroid focal lesions - Maciej Ratajczak; Małgorzata Gietka-Czernel (Wiedza Medyczna, 2020)
The occurrence of focal lesions in the thyroid gland affects up to 65% of the general population, and an important element of diagnostics is the most precise possible distinction between benign and malignant lesions. Despite advanced knowledge and developed algorithms, in some cases the decision to proceed further may cause problems even for an experienced clinician. A promising tool in estimating oncological risk is sonoelastography. This article aims to approximate and organize knowledge in this field in relation to focal lesions of the thyroid gland and to encourage the implementation of the method in everyday practice.